2013
DOI: 10.1371/journal.pntd.0002269
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Active Site of the Collagenolytic Cathepsin L3 Protease of the Invasive Stage of Fasciola hepatica

Abstract: BackgroundA family of secreted cathepsin L proteases with differential activities is essential for host colonization and survival in the parasitic flatworm Fasciola hepatica. While the blood feeding adult secretes predominantly FheCL1, an enzyme with a strong preference for Leu at the S2 pocket of the active site, the infective stage produces FheCL3, a unique enzyme with collagenolytic activity that favours Pro at P2.Methodology/Principal FindingsUsing a novel unbiased multiplex substrate profiling and mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 39 publications
7
37
0
Order By: Relevance
“…Cleavage sites that were sensitive to AEBSF had a trypsin-like substrate specificity profile using the MSP-MS assay. Interestingly, the cleavage sites that were sensitive to E-64 also had a strong P1 preference for Arg and Gln and generally accepted hydrophobic residues at P2, consistent with that known for cysteine cathepsins [7577]. …”
Section: Resultssupporting
confidence: 64%
“…Cleavage sites that were sensitive to AEBSF had a trypsin-like substrate specificity profile using the MSP-MS assay. Interestingly, the cleavage sites that were sensitive to E-64 also had a strong P1 preference for Arg and Gln and generally accepted hydrophobic residues at P2, consistent with that known for cysteine cathepsins [7577]. …”
Section: Resultssupporting
confidence: 64%
“…Secretion of hydrolytic enzymes has been associated with virulence in pathogenic bacteria, parasites, 3 and fungi. 4 Secreted aspartyl proteinases have been extensively studied and investigations have demonstrated that they play a role in the virulence of both C. albicans 5 and C. parapsilosis.…”
Section: Introductionmentioning
confidence: 99%
“…Fasciola cathepsin L3 is capable of degrading the proline-rich triple helical regions of collagen while cathepsin L1 cannot (Corvo et al 2013). We can therefore deduce that H. americanus cathepsin L2 is likely to be the enzyme responsible for the collagen-degrading activity in gastric juice (Chen 1991).…”
Section: Discussionmentioning
confidence: 99%